The Phillips curve and the role of monetary policy in Chile - Leonardo Salazar (Journal of Applied Economics, 2019)
In this paper, the empirical analysis finds that the dynamics of inflation and unemployment can be described by a Phillips curve when allowing for a positive co-movement between trend-adjusted productivity and unemployment. This suggests that improvements in productivity have been achieved by laying off the least productive part of the labor force. Furthermore, the natural rate of unemployment is a function of the long-term interest rate, indicating that monetary policy is not completely neutral in the long run. This result rejects the natural rate hypothesis and, at the same time, provides empirical support for the structural slump theory in a world of imperfect knowledge. The recent theory of imperfect knowledge economics (IKE) seems to address the problem that many economic models lack: persistence in the observed data. By combining IKE and the structural slumps theory it is possible to obtain predictions that are theoretically and empirically consistent.